Bisphosphonate-Related Osteonecrosis of the Jaw Mimicking Bone Metastasis. (30th January 2014) - Bhatt, Geetika; Bhatt, Aashish; Dragun, Anthony E.; Li, Xiao-Feng; Civelek, A. Cahid
Abstract : Osteonecrosis of the jaw is usually a potential complication of bisphosphonate therapy. In a cancer patient, this disease entity can be misdiagnosed as a metastatic lesion. Our aim is to make clinicians aware of bisphosphonate associated osteonecrosis of the jaw to prevent misdiagnosis and initiate proper treatment at the earliest. We present the case of a breast cancer patient with multiple bony metastases and a jaw lesion presumed to be metastases. After no response to palliative radiation, repeat radiological imaging studies revealed osteonecrosis of the jaw. Correlating a patient's clinical information with findings on diagnostic imaging studies, such as SPECT bone and CT scans, can help identify this potential complication of bisphosphonate treatment. Early diagnosis helps minimize unnecessary biopsies and allows for the proper treatment to be instituted.